2022
DOI: 10.3389/fpsyt.2022.1095254
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand smoke is positively associated with pre-frailty and frailty in non-smoking older adults

Abstract: IntroductionEither exposure to secondhand smoke (SHS) or frailty has been linked to adverse health outcomes in nonsmoking adults. However, their relationship is rarely studied. The purpose of this study is to examine the association between serum cotinine level and frailty status among non-smoking older adults.MethodThe study population consisted of 2,703 older adults aged ≥60 from the National Health and Nutrition Examination Survey 2011–2014. Non-smokers were included based on (1) a serum cotinine level ≤ 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
1
9
0
1
Order By: Relevance
“…In the present study, we categorized participants' plasma levels of lead into four groups based on quartile and used the 1st quartile (the lowest quartile) as a reference. This is consistent with prior NHANES-based epidemiological studies (Fu et al, 2022a , b ; Li et al, 2023 ).…”
Section: Methodssupporting
confidence: 92%
“…In the present study, we categorized participants' plasma levels of lead into four groups based on quartile and used the 1st quartile (the lowest quartile) as a reference. This is consistent with prior NHANES-based epidemiological studies (Fu et al, 2022a , b ; Li et al, 2023 ).…”
Section: Methodssupporting
confidence: 92%
“…In this group of 2,296 older adults, we found that 3 4 of them had either pre-frailty or frailty. Compared to robust, frailty was independently associated with worse DSST and global cognition z-scores.…”
Section: Discussionmentioning
confidence: 74%
“…Frailty is characterized by a compromised ability to respond to external stimuli. It is associated with a long-term cumulative decline in reserves and functions in multiple systems in the human body ( 2 , 3 ). Pre-frailty is a latent condition that increases a person’s risk of frailty and typically occurs before clinically identifiable frailty ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Secondhand smoke is also associated with a higher incidence of both pre‐frailty and frailty. Fu et al 22 . investigated the data of non‐smokers obtained from the US National Health and Nutrition Examination Survey, and found that higher serum cotinine levels are associated with an increased risk of pre‐frailty and frailty in non‐smoking older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Kaskirbayeva et al 21 identified smoking as one of the risk factors for the progression of frailty in older adults. Fu et al 22 used a registered database and found that not only does tobacco smoking negatively affect frailty prevention, but secondhand smoking also plays a role in determining frailty and pre-frailty. Also, previous studies and meta-analyses showed that there was a significantly increased likelihood of frailty in patients with chronic bronchitis or chronic obstructive pulmonary disease, and chronic obstructive pulmonary disease is a common chronic disease among people with a smoking habit.…”
Section: Introductionmentioning
confidence: 99%